The Effect of Lemon Peel (Citrus limon) Aromatherapy Inhalation as Antidepressant on Rats using Diffuser Method - Indra Setiawan; Iwan Sis Indrawanto; Abi Noerwahjono; Abdi Malik Rahardjo (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2021)
Abstract. Background Depression is a mood disorder that affects a person’s quality of life. This condition is influenced by the levels of monoamine compounds such as serotonin, norepinephrine, and dopamine in the brain. The decrease in monoamine levels leads to depressive symptoms. Lemon peel essential oil has an antidepressant potential, that contains phytochemicals, d-Limonene, which increase monoamine levels in the brain. Aromatherapy diffuser inhalation method is one kind of treatment route in depression. The mechanism of action is by breaking down the smaller essential oil particles so they penetrate quicker to the brain. Objective: To determine the effect of lemon peel (Citrus limon) aromatherapy inhalation diffuser method on immobility time of white rats (Rattus norvegicus Wistar strain) on the tail suspension test. Method: True Experimental with Post Test Only Control Group Design. Fifteen white male rats Wistar strain were divided into 5 groups. The positive control group was given stressors and saline induction intraperitoneally. In addition to stressors, the treatment group was also given lemon peel aromatherapy inhalation at a dose of 1%, 2.5%, and 5%. Measurement of immobility time was carried out by hanging the rats' tails through the tail suspension test method and the time of animals stopped moving for at least 1 second was calculated using a timer. Data were analyzed using the ANOVA test, Post Hoc test, Pearson correlation test, and Linear Regression test. Results and Discussion: ANOVA test showed a significant difference between groups (p = 0.017). The post Hoc test showed a significant difference (p <0.05) between the positive control and the P3 group (5%). The linear regression test obtained Adjusted R2 = 0.598 (inhalation of lemon peel aromatherapy gives an effect of 59.8%). The decrease of immobility time was due to the reduction of depression that was caused by the increase of monoamine level induced by d-limonene in lemon peel essential oil. Conclusion: The inhalation of lemon peel (Citrus limon) aromatherapy with diffuser method has the antidepressant effect that reduces the immobility time of depressed white rats (Rattus norvegicus Wistar strain).